Cara Pandang Baru atas Perbedaan Agama Kristiani dan Islam (Sumbangan Strukturalisme Levi-Strauss dalam menganalisis Perbedaan Agama) - Listia Listia (Jurnal Orientasi Baru, 2011)
In dealing with problems of modernity, religious communities should developa cooperation which is enable to construct a system based on common ethics,which gives support to the implementation of the mandate of humanity, in linewith the vision of all religions. This article offers an alternative of the way ofthinking on the differences between Christianity and Islam.Based on Levi-Strauss structuralism, there are two points offered in this article.The first is the paradigm and methodology needed to find out alternative wayof thinking on the religious differences. The second is the application of themethodology which produces new insights of these differences.The new point presented in this article are that the differences of religions canbe traced from the reality that each culture has beliefs on the Absolute whichhas a relationship with the human being with its implications. Differences doesnot mean negation to one another if we can understand the various parts of thedoctrines in the whole context and in the relationship with other elements of thewhole system.